A survey of tree planting in Somalia 1925-1985 - Bowen, M (Oxford Forestry Institute, University of Oxford, 1988)
The names and locations of past and present organisations involved in tree planting in Somalia are listed. In total, about 30 projects of both government and non-governmental agencies have planted perhaps ten million trees and tested some 215 species during the past 60 years. Many of these plantings have taken place as shelterbelts or windbreaks (equivalent to about 1,600 ha) or for amenity purposes. Block plantations have been established to stabilise both coastal and inland sand dunes on about 1,500 ha (a lower estimate than the previously published figures), while about 1,800 ha have been established as community wood lots. Fruit trees form a sizeable proportion of amenity plantings. There has generally been excessive optimism as to what species, especially exotics, will grow successfully. It is premature to make firm species recommendations for the different Somali ecological zones, most of which are arid or semi-arid and frequently have saline soils. On the sand dunes Casuarina equisetifolia, Acacia nilotica, A.holosericea, Prosopis juliflora, P.chilensis and Anacardium occidentale appear promising. In the harsh rangelands, various exotic species and indigenous acacias have shown good survival and growth, including Prosopis species and Parkinsonia aculeata. Azadirachta indica and Conocarpus lancifolius grow well where ground water is near the surface. Various eucalypts, as well as some of the species mentioned previously, show promise on the northern hills and on irrigated farmland.